The Flavonoids Hesperidin and Diosmin: Adjuvant Therapy for Obesity - Sanjay Kalra; Atul Dhingra; Suneet Kumar Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
The flavonoids are polyphenolic plant products, characterized by a 15-carbon skeleton which includes two benzene rings. Two active flavonoids, diosmin and hesperidin, are used as venotonic and vasculoprotective agents in clinical practice. They are indicated for the management of varicose veins, chronic venous insufficiency and haemorrhoids. They help improve circulatory tone, reduce inflammation, strengthen venous walls, and alleviate symptoms such as discomfort, pain and swelling. In this communication, we explore their potential use in obesity, especially obesity related oedema (obestasis). Keywords: Daflon, lymphatic, obesity, oedema, overweight, venous disorders